Gender Differences in Tournament Choices: Risk Preferences, Overconfidence or Competitiveness? - Roel van Veldhuizen (Journal of the European Economic Association, 2022)
A long line of laboratory experiments has found that women are less likely to sort into competitive environments. Although part of this effect may be explained by gender differences in risk attitudes and self-confidence, previous studies have attributed the majority of the gender gap to gender differences in a competitiveness trait. I re-examine this result using a novel experiment that allows me to separate competitiveness from alternative explanations using causal treatments. In contradiction to the main conclusion drawn in a long literature, my results imply that the entire gender gap is driven by gender differences in risk attitudes and self-confidence, which has implications for policy and research.
Keywords: C90; D01; J16; 330